TRANSLATOR’S PREFACE AS A GENRE: A COMPARATIVE ANALYSIS OF LITHUANIAN AND ENGLISH PREFACES - Bikmanienė, Milda (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
Translations serve as a right to the international existence as they allow the national literature to reach wider audiences. Moreover, they allow readers to get acquainted with literature of other cultures. For these reasons, translators have an important role in the literary world. Translators’ prefaces are the main link between readers and translators. However, there is a lack of analysis of this specific genre. This research aims at analysing translator’s preface as a genre and examining differences and similarities of genre features in Lithuanian and English prefaces. 30 Lithuanian and 30 English translators’ prefaces are analysed according to genre elements, such as the format, genre moves and functions. The analysis covers a wide range of examples of both Lithuanian and English fiction books. For this reason, the analysed translators’ prefaces are published in different years, are translated by different translators and are published by different publishing houses. It may be noted, that the analysis reveals that Lithuanian translators tend to be more invisible in their prefaces than English translators. They focus on the author and provide little of their own evaluation and explicit explanations on translation issues. However, English translators focus on the translation process and the subjective analysis. The analysis also demonstrates that the basic format of prefaces is beginning with a title and ending with a signature.